2020
DOI: 10.1007/s11357-020-00167-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy to gene editing: potential therapeutic approaches for Hutchinson–Gilford progeria syndrome

Abstract: Hutchinson-Gilford progeria syndrome (HGPS), commonly called progeria, is an extremely rare disorder that affects only one child per four million births. It is characterized by accelerated aging in affected individuals leading to premature death at an average age of 14.5 years due to cardiovascular complications. The main cause of HGPS is a sporadic autosomal dominant point mutation in LMNA gene resulting in differently spliced lamin A protein known as progerin. Accumulation of progerin under nuclear lamina an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 244 publications
(314 reference statements)
0
9
0
Order By: Relevance
“…However, quite a few compounds that can prevent their formation have been identified. These compounds (in particular, sulforaphane, metformin, rapamycin) cleave prelamin A and progerin by autophagic degradation [ 924 , 925 ] ( Table 3 ).…”
Section: Pharmacological Interventions Protecting Genomementioning
confidence: 99%
“…However, quite a few compounds that can prevent their formation have been identified. These compounds (in particular, sulforaphane, metformin, rapamycin) cleave prelamin A and progerin by autophagic degradation [ 924 , 925 ] ( Table 3 ).…”
Section: Pharmacological Interventions Protecting Genomementioning
confidence: 99%
“…For protein accumulation diseases such as the laminopathies, HGPS and NDs, removal of the cytotoxic proteins through genetic manipulation would provide cures. The hope for the future is the use of novel technologies, such as CRISPR-Cas9-mediated genome editing [152][153][154], to correct these genetic defects by, for example, silencing the dominant-negative allele of LMNA or upregulating autophagy genes. HGPS mouse models edited by CRISPR-Cas9 have shown the potential of this.…”
Section: Manipulating For Lamina Protein Clearancementioning
confidence: 99%
“…A previous study reported that the accumulation of progerin in HGPS cells leads to aberrant nuclear morphology, genetic instability, and p53-dependent premature senescence [64] . Progerin and prelamine A inhibition may provide potential therapeutic approaches to the removal of cellular senescence [ 65 , 66 ]. Numerous studies have shown that p53/p21 pathway is involved in regulating cellular senescence 67 , 68 , 69 .…”
Section: Introductionmentioning
confidence: 99%